Trends in credit market arbitrage - Nina Boyarchenko; Pooja Gupta; Nick Steele; Jacqueline Yen (Federal Reserve Bank of New York, 2016)
Market participants and policymakers alike were surprised by the large, prolonged dislocations in credit market arbitrage trades during the second half of 2015 and the first quarter of 2016. In this paper, we examine three explanations proposed by market participants: increased idiosyncratic risks, strategic positioning by some market participants, and regulatory changes. We find some evidence of increased idiosyncratic risk during the relevant period but limited evidence of asset managers changing their positioning in derivative products. While we cannot quantify the contribution of these two channels to the overall spreads, the relative changes in idiosyncratic risk levels and in asset managers' derivatives positions appear small relative to the post-crisis increase in cost of capital. We present the mechanics of the CDS-bond arbitrage trade, tracing its impact on a stylized dealer balance sheet and the return-on-equity (ROE) calculation. We find that, given current levels of regulatory leverage, the CDS-bond basis would need to be significantly more negative relative to pre-crisis levels to achieve the same ROE target.
Keywords: G10; G23; G28; 330; CDS basis; capital requirements; M-CAPM